PENGARUH LAYANAN BIMBINGAN KLASIKAL DENGAN METODE PROBLEM BASED LEARNING TERHADAP PENGETAHUAN DAMPAK BURUK PROKRASTINASI AKADEMIK PADA SISWA - Laela Nurhaliza; Rahmawati Rahmawati; Arga Satrio Prabowo (Jurnal Penelitian Bimbingan dan Konseling, 2023)
The aim of this research is to determine the effect of classical guidance services using the problem based learning method on understanding the negative impacts of student academic procrastination. This research applies a Quasi Experimental research form using Nonequivalent Control Group Design. The population in this study was 225, who were all 11th grade students for the 2023/2024 academic year at Pasundan 1 Vocational School, Serang City. The sampling technique used a cluster random sampling technique which resulted in class 11 AKL becoming the experimental class and class 11 BDP becoming the control group. Data collection techniques include test questions and observations. The test instrument used is in the form of multiple choice for the pretest and posttest to measure knowledge of the negative impact of academic procrastination on students. The instrument was tested through 3 tests, namely the discrimination test, difficulty test, and distractor effectiveness test. The results of the analysis test using Mann-Whitney obtained a mean value in the experimental group of 27.67 while the mean value in the control group was 10.79. Then, the results of the hypothesis test show that Asymp.Sig (2 tailed) is 0.000, so it can be concluded that the use of the problem based learning method can have a significant influence on knowledge of the negative impacts of academic procrastination for grade 11 AKL students at Pasundan Vocational School, Serang City.Keywords: Problem based learning methods, Knowledge bad impact of academic procrastination